2014
DOI: 10.1155/2014/506273
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Decyl Gallate against Several Species of Pathogenic Fungi

Abstract: This work aims to demonstrate that the gallic acid structure modification to the decyl gallate (G14) compound contributed to increase the antifungal activity against several species of pathogenic fungi, mainly, Candida spp., Cryptococcus spp., Paracoccidioides spp., and Histoplasma capsulatum, according to standardized microdilution method described by Clinical Laboratory Standard Institute (CLSI) documents. Moreover this compound has a particularly good selectivity index value, which makes it an excellent can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
(44 reference statements)
0
10
0
Order By: Relevance
“… Gullo et al (2012) evaluated natural and semi-synthetics compounds such as maytenin and pristimerin and observed excellent minimum inhibitory concentration against different isolates of P. brasiliensis . In the same way, de Paula et al (2014) evaluated the antifungal activity of the Alkyl gallates, which presented important biological activity reported by the literature, against different fungi species, including different isolates of P. brasiliensis and P. lutzii . They observed that these molecules presented important relations between the structure and activity, and that the decyl gallate have special activity against Paracoccidioides species.…”
Section: Facing the Problem: Through The Diagnostic To Treatment Of Pmentioning
confidence: 99%
“… Gullo et al (2012) evaluated natural and semi-synthetics compounds such as maytenin and pristimerin and observed excellent minimum inhibitory concentration against different isolates of P. brasiliensis . In the same way, de Paula et al (2014) evaluated the antifungal activity of the Alkyl gallates, which presented important biological activity reported by the literature, against different fungi species, including different isolates of P. brasiliensis and P. lutzii . They observed that these molecules presented important relations between the structure and activity, and that the decyl gallate have special activity against Paracoccidioides species.…”
Section: Facing the Problem: Through The Diagnostic To Treatment Of Pmentioning
confidence: 99%
“…Decyl gallate (G14). G14 was obtained and provided by Instituto de Química, UNESP (Araraquara, Brazil), according to Morais et al (35) and prepared according to de Paula e Silva et al (8).…”
Section: Methodsmentioning
confidence: 99%
“…Our group demonstrated that decyl gallate (G14) had great antifungal activity in vitro against 18 pathogenic fungi species (including eight different Paracoccidioides isolates). For Paracoccidioides isolates, G14 presented a low MIC and a good selectivity index value (Ͼ10) against infection in human lung epithelial cells (A549) and normal fibroblast pulmonary cells (MRC-5) (8). These results showed that G14 is an excellent candidate for a broad-spectrum antifungal prototype and encouraged us to try to discover its mechanism of action.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Potential compounds act as growth inhibitors against Paracoccidioides spp. in low concentrations ( Table S1 ), such as alkyl gallates (0.004–16 µg/mL), an N-Glycosylation inhibitor [ 38 , 39 ]; the thiosemicarbazone lapachol, which acts on the plasma membrane (0.01–0.1 µM) [ 40 ]; azasterol analogs (0.5–10 µM) [ 41 ] and hydrazone derivatives (0.1–5 µM) [ 42 ], as inhibitors of ergosterol biosynthesis. These compounds are less potent when compared to azole derivatives, such as itraconazole with a 0.003–0.05 µM MIC [ 33 ]; luliconazole, a topical antifungal repositioned against Paracoccidioides spp.…”
Section: New Anti- Paracoccidioides Compounds: mentioning
confidence: 99%